Autophagic pathways to clear the tau aggregates in alzheimer's disease - Gorantla, Nalini Vijay; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Tau is a microtubule-associated protein with an intrinsically unstructured conformation. Tau is subjected to several pathological post-translational modifications (PTMs), leading to its loss of interaction with microtubules and accumulation as neurofibrillary tangles (NFTs) in neurons. Tau aggregates impede functions of endoplasmic reticulum and mitochondria leading to the generation of oxidative stress and in turn amplifying the Tau aggregation. Tau is channelled to chaperones for folding into their native form, which otherwise causes its degradation and clearance. Cellular response triggers the activation of ubiquitin-proteasome system or autophagy to facilitate Tau degradation, based on the PTMs or mutations associated with Tau. Further, autophagy can be selective where Hsc70 interacts with Tau in monomeric, oligomeric and aggregated form and drives its clearance by chaperone-mediated autophagy pathway (CMA). Lysosome-associated membrane proteins-2A (LAMP-2A) is the key player of CMA that recognises Hsc70-Tau complex and triggers the downstream cascade. Thus, it becomes challenging for mutant Tau to be cleared by CMA as it loses its affinity for Hsc70 and LAMP-2A. In such a scenario, Tau might be degraded by macroautophagy otherwise sequestered by aggresomes. Henceforth, the degradation of Tau and its blockage that is associated with various PTMs of Tau would explain the dynamics of Tau degradation or accumulation in AD. Further, unveiling the role of accessory proteins involved in these degradation pathways would help in understanding their loss of function and preventing Tau clearance.
Keywords: Alzheimer's disease; Chaperone-mediated autophagy; Lysosome-associated membrane proteins-2A; Macroautophagy; Neurofibrillary tangles; Tau; Tau degradation; Ubiquitin-proteasome system

Implications of valosin-containing protein in promoting autophagy to prevent tau aggregation - Chinnathambi, Subashchandrabose; Gorantla, Nalini Vijay (Neuroscience, 2021)
and cellular degradative mechanisms modulate Tau aggregation. During aging and neu-rodegenerative disorders, the cellular proteostasis is disturbed due to impaired protective mechanisms. This results in accumulation of aberrant Tau aggregates in the neuron that leads to microtubule destabilization and neuronal degeneration. The intricate mechanisms to prevent Tau aggregation involve chaperones, autophagy, and proteasomal system have gained main focus about concerning to therapeutic intervention. However, the thor-ough understanding of other key proteins, such as Valosin-containing protein (VCP), is limited. In various neu-rodegenerative diseases, the chaperone-like activity of VCP is involved in preventing protein aggregation and mediating the degradation of aberrant proteins by proteasome and autophagy. In the case of Tau aggregation associated with Alzheimer's disease, the importance of VCP is poorly understood. VCP is known to co-localize with Tau, and alterations in VCP cause aberrant accumulation of Tau. Nevertheless, the direct mechanism of VCP in altering Tau aggregation is not known. Hence, we speculate that VCP might be one of the key modulators in preventing Tau aggregation and can disintegrate Tau aggregates by directing its clearance by autophagy. = 2021 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: Autophagy; segregase; Tau aggregates; Ubiquitin-proteasome system; valosin-containing protein